Strategi Live Streaming dalam Meningkatkan Daya Saing UMKM di Era Ekonomi Digital: Analisis Perilaku Belanja Konsumen - Asmawati Halilah Damanik; Heru Sugara; Victor Marudut Mulia Siregar (Owner : Riset dan Jurnal Akuntansi, 2025)
The rapid growth of the digital economy requires Micro, Small, and Medium Enterprises (MSMEs) to adopt technology-based marketing strategies. Live streaming has become a potential strategy as it enables direct interaction with consumers, builds trust, and expands market reach; however, its use among MSMEs in Simalungun Regency remains limited. This study aims to analyze the influence of live streaming strategies on MSME competitiveness by considering consumer purchasing behavior. A mixed-methods explanatory design was applied, combining quantitative surveys analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with qualitative approaches through interviews, focus group discussions, and observations. The sample consists of at least 100 respondents, including MSME owners and consumers. The study is expected to produce a contextual digital marketing model based on live streaming, a mapping of consumer content preferences, and recommendations for effective social media platforms. The findings are expected to strengthen MSME competitiveness and support sustainable digital transformation